If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -68 + -1(-25) = 0 Multiply -1 * -25 -68 + 25 = 0 Combine like terms: -68 + 25 = -43 -43 = 0 Solving -43 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| N+1=3n+9 | | (xy)dx+(x+1)dy=0 | | 0.95x+0.05(2-x)=0.10(163) | | 4z^2-4x=24 | | 12 = k2 + 10 | | 72x^2-8x+9=0 | | 3.5+(-7.5)= | | -1-6p=6-7p | | n-9-9n=1-7n | | 7=2g+3 | | 6+6n=-4(2-5n) | | 3.5+(7.5)= | | 28-6x=49-9x | | (X+1)=x | | 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n | | 88=12x-44 | | 16x-16-8x-12=3 | | 9-4b=4-3b-6b | | 16-(2x-3)=6 | | 6x-14=2(3x-72) | | 11x-13=5(2x+4)-7 | | 45=29-2(x-3) | | 2x^2-y^2-8x+6y-2=0 | | 8a+10=50 | | 7+7k=8k+2 | | -6m+3m=4-m |